Bangladesh Policy Note : Procurement Management Capacity Development in Bangladesh - World Bank (Washington, DC, 2013)
Bangladesh has reshaped the landscape of procurement policy reform and capacity development over the last several years, and has taken lead in the South Asia region. Though reasonably good progress has been made in policy reform, yet its application has proven to be relatively inconsistent. Effective implementation of the law requires a public and a private sector that have the skills and ability to plan, execute, monitor, and manage procurement. Efficient management of public procurement is largely dependent on the adequacy of understanding and skill of procurement professionals involved in the process. The World Bank supported Government's procurement reform as part of its strategy to improve governance. Yet efforts to improve procurement systems will have little effect to ensure best value for money if these systems are not implemented by professionals of adequate knowledge and expertise. Skill gap in the area of procurement is a recognized fact. And continuation of the capacity development activity is crucial to bring about an effective change in the system. The policy note is designed to provide guidance/ advice to Government of Bangladesh (GOB) in: (i) developing a robust framework for procurement capacity development, covering government/public/private sector entities including contractors, suppliers, and consultants; and (ii) establishing a mechanism to institutionalize procurement management capacity in Bangladesh and make it effective and sustainable with tangible benefits on the ground.